Risk factors for in-hospital death in 2,179 patients with acute aortic dissection - Yuan, Yue; Xia, Zhiyu; Wang, Lei; Sun, Qi; Wang, Wendan; Chai, Chen; Wang, Tiantian; Zhang, Xiaowei; Wu, Long; Tang, Zehai (Frontiers in Cardiovascular Medicine, 2023)
Background This study aims to investigate the risk factors for in-hospital death in patients with acute aortic dissection (AAD) and to provide a straightforward prediction model to assist clinicians in determining the outcome of AAD patients. Methods Retrospective analysis was carried out on 2,179 patients admitted for AAD from March 5, 1999 to April 20, 2018 in Wuhan Union Hospital, China. The risk factors were investigated with univariate and multivariable logistic regression analysis. Results The patients were divided into two groups: Group A, 953patients (43.7%) with type A AAD; Group B, 1,226 patients (56.3%) with type B AAD. The overall in-hospital mortality rate was 20.3% (194/953) and 4% (50/1,226) in Group A and B respectively. The multivariable analysis included the variables that were statistically significant predictors of in-hospital death (P < 0.05). In Group A, hypotension (OR = 2.01, P = 0.001) and liver dysfunction (OR = 12.95, P < 0.001) were independent risk factors. Tachycardia (OR = 6.08, P < 0.001) and liver dysfunction (OR = 6.36, P < 0.05) were independent risk factors for Group B mortality. The risk factors of Group A were assigned a score equal to their coefficients, and the score of −0.5 was the best point of the risk prediction model. Based on this analysis, we derived a predictive model to help clinicians determine the prognosis of type A AAD patients. Conclusions This study investigate the independent factors associated with in-hospital death in patients with type A or B aortic dissection, respectively. In addition, we develop the prediction of the prognosis for type A patients and assist clinicians in choosing treatment strategies.